INTERNET OF THINGS (IOT) BASED TEMPERATURE AND HUMIDITY MONITORING IN CHICKEN CAGES: MONITORING SUHU DAN KELEMBABAN BERBASIS INTERNET OF THINGS (IOT) PADA KANDANG AYAM - Bagus , Hendri; Atiq, Muhammad; Nuri (Edukasi Elektromatika, 2022)
n the condition of chickens aged 0 -15 days, it is necessary to have a temperature condition in the cage ranging from 25 ℃ to 33 ℃, it is necessary to have a tool for monitoring the temperature and humidity of the chick coop and automatic temperature control. Several previous studies have discussed monitoring the temperature and humidity of chicken coops, including Design and Development of Monitoring Temperature and Humidity of Cages to Facilitate Arduino-Based Livestock Performance. Subsequent research discusses the Automatic Temperature Control and Monitoring System for Chicken Coops in Sukamanis Village Based on Arduino. The method applied to this system is using the SDLC method and the microcontroller used is Arduino. Subsequent research discusses monitoring the temperature and humidity of the chicken coop according to the age of the chickens. Several previous studies used ESP8266 while researchers used the GSM SIM 800L module for monitoring with a GSM network connection. The test results show that the DHT11 sensor will read the temperature and humidity conditions in the chicken coop room and display it on the 16X2 LCD and thingspeak in real time. While the prototype automatic system, the lights will turn on if the room temperature is below the provisions while the fan will turn on if the temperature in the room is above the provisions. Pada kondisi ayam usia 0 -15 hari di perlukannya sebuah kondisi suhu pada kandang berkisar 25℃ sampai 33℃, maka perlu dilakukannya sebuah alat untuk monitoring suhu dan kelembaban kandang anak ayam dan kontrol suhu otomatis. Beberapa penelitian sebelumnya telah membahas tentang monitoring suhu dan kelembaban kandang ayam diantaranya, Rancang Bangun Monitoring Suhu Dan Kelembaban Kandang Guna Mempermudah Kinerja Peternakan Berbasis Arduino. Penelitian selanjutnya membahas tentang Sistem Monitoring Dan Pengatur Suhu Otomatis Untuk Kandang Ayam Di Desa Sukamanis Berbasis Arduino Metode yang di terapkan pada sistem ini yaitu menggunakan metode SDLC dan mikrokontroler yang digunakan yaitu Arduino. Penelitian berikutnya membahas tentang monitoring suhu dan kelembapan kandang ayam yang sesuai dengan usia ayam. Beberapa penelitian sebelumnya menggunakan ESP8266 sedangkan peneliti menggunakan modul GSM SIM 800L untuk monitoring dengan koneksi jaringan GSM. Hasil pengujian menunjukkan sensor DHT11 akan membaca kondisi suhu dan kelembaban pada ruangan kandang ayam dan ditampilkan pada LCD 16X2 dan thingspeak secara real time. Sedangkan sistem otomatis protipe, lampu akan menyala jika suhu ruangan dibawah ketentuan sedangkan kipas akan menyala jika suhu pada ruangan diatas ketentuan